Peningkatan Kemampuan Menyimak melalui Mendongeng dan Artikulasi - Deprianus Zalukhu; Agustina Harefa (CV. SINAR HOWUHOWU, 2024)
Education is a lifelong learning process that includes all efforts to foster and develop individuals holistically. Various studies show that listening and speaking skills have an important role in children's language development. Listening skills, especially through storytelling activities, can enrich their language and communication skills, providing a foundation for speaking, reading and writing skills. Storytelling is not only educational but also builds morals and cultural values. In addition, the articulated learning model focuses on students' active participation in learning, which can improve comprehension, critical thinking and social skills. Through this method, students learn to convey messages effectively, which strengthens their receptive and expressive language skills.